2021
DOI: 10.3138/jelis.62.1-2018-0053
|View full text |Cite
|
Sign up to set email alerts
|

Digital Preservation in LIS Education: A Content Analysis of Course Syllabi

Abstract: Following a revolution in digital information and technological development, both the need for and opportunities in digital preservation education have been growing over the last 30 years. This study aimed to examine digital preservation course content through an analysis of course syllabi to understand what is taught in library schools through the graduate level. Our analysis demonstrates the significant growth in digital preservation education during the last decade but also presents several areas that need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Surprisingly, some faculty introduced no technology; others crammed in as many tools as feasible given curriculum, course delivery method, and IT support constraints; and still others fell in between, but toward the lower end. Faculty members' overall tendency to teach only a few tools supports Yoon et al (2021).…”
Section: Tools and Technologies Archival Faculty Enlist In Their Teac...mentioning
confidence: 99%
See 3 more Smart Citations
“…Surprisingly, some faculty introduced no technology; others crammed in as many tools as feasible given curriculum, course delivery method, and IT support constraints; and still others fell in between, but toward the lower end. Faculty members' overall tendency to teach only a few tools supports Yoon et al (2021).…”
Section: Tools and Technologies Archival Faculty Enlist In Their Teac...mentioning
confidence: 99%
“…To this end, a recent study of 60 American Library Association-accredited programs found that 35 (58.3%) offered total of 59 digital curation or preservation courses (Yoon et al, 2021). This was a marked increase over the late 2000s (Gracy & Croft, 2007) and early 2010s (Creamer et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Hal ini senada dengan apa yang disampaikan oleh David dan Saskis (2020). Selain itu, RPS yang baik memuat informasi tentang identitas lainnya (Ayoung Yoon, Murillo, & McNally, 2021;David & Zazkis, 2020;Denton & Veloso, 2018;Junaidi dkk., 2020;Parkes & Harris, 2002), termasuk di dalamnya mengenai deskripsi MK (David dan Zazkis 2020;Denton dan Veloso 2018;Max 2021;Saundersa 2015;Wolfe 2005).…”
Section: Pembahasanunclassified